Admissions Constraints and the Decision to Delay University. (9th October 2020) - Foley, Kelly; Groes, Fane
Abstract: We investigate whether delaying entrance into university is affected by restrictions on admissions into competitive programs. Using Danish administrative data, we estimate a dynamic discrete choice model, in which students choose, if admitted, either to enter one of 30 programs or to delay. We use the model to examine delaying choices under different simulated admissions policies. Our experiments suggest that only 28 percent of students who delay do so because of admissions restrictions. Furthermore, although students respond to admissions incentives, our results imply that such policies are unlikely to substantially change the overall distribution of delay.